PENGARUH INDEPENDENSI KOMITE AUDIT, AUDIT TENURE DAN REPUTASI AUDITOR TERHADAP KUALITAS AUDIT PADA PERUSAHAAN SEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2011-2018 - Kartika Aprilia Aridi; Yumniati Agustina (Politeknik Negeri Jakarta, 2019)
This study aims to analyze the effect of the independence of the audit committee, audit tenure and auditor's reputation on audit quality in retail trading companies listed on the Indonesia Stock Exchange in 2011-2018. This research is an associative research with quantitative methods. In this study obtained 7 sample companies that meet the criteria. Data analysis and hypothesis testing techniques in this study used logistic regression analysis. Nagelkerke R Square test results of 0.225, which shows that audit quality can be explained by the independence of the audit committee, audit tenure and auditor's reputation of 22.5%. The independence of the audit committee obtained a significance value of 1,000, audit tenure obtained a significance value of 0.710 did not affect the audit quality, the auditor's reputation gained a significance value of 0.021 so that it significantly affected the audit quality. The independence of the audit committee, audit tenure and auditor reputation in the Omnibus Test of Model Coefficients table obtained a Chi-square value of 9,048 with a significance level of 0.029 <0.05 indicating that jointly (simultaneously) influences the audit quality